Emerging Powers in the WTO Developing Countries and Trade in the 21st Century - Michalopoulos, C. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This volume examines the main factors for developing country trade performance in the last thirty years, their own trade policies, market access issues they face, and their increasingly more effective participation in the WTO and the Doha Round of multilateral trade negotiations.